The effect of wind on extensive lightweight vegetated roofs - Sukopova Dagmar; Mohapl Martin (E3S Web of Conferences, 2024)
Nowadays, Lightweight vegetated roofs are becoming increasingly popular due to their light weight, low maintenance and water consumption. Even though they are mostly extensive greenery (staghorn bushes, mosses, etc.) they can provide urban areas with a few benefits. In particular, they can make an important contribution to improving the urban microclimate and reducing the negative urban heat island effect. They also contribute to the conservation of biodiversity by providing alternative refuges for a range of animals. However, due to their light weight, these lightweight systems may not withstand adverse weather conditions well, especially at the beginning of their construction. Wind resistance can cause them to erode and wind erosion of the growing medium can occur, especially when the root network is not yet sufficiently anchored in the vegetation system. Roof sections may be rotated, displaced, or even overturned, especially in the outer parts of the roof. The effects of wind action can also be influenced by the slope of Lightweight roofs. Roofs with a pitch of less than 30° may be subject to stronger wind suction effects. Existing research shows that, for example, roofs with a pitch greater than 35° have better resistance to wind pressure. This paper discusses different variants of existing solutions to the given problem.